(untitled) (Eurasian Medical Research Periodical, 2023)
Maternal mortality is an integrating indicator of the health of women of reproductive age and reflects the population outcome of economic, socio-hygienic and medicoorganizational factors, is an indicator characterizing the activities of the women’s and children’s health service. The article presents the risk factors of maternal mortality, analyzes the primary medical documentation of 70 deceased women in the Samarkand region of the Republic of Uzbekistan, evaluates the quality and error analysis, and provides ways to reduce it.